1992
DOI: 10.1037/0022-3514.62.6.893
|View full text |Cite
|
Sign up to set email alerts
|

The generality of the automatic attitude activation effect.

Abstract: and Kardes (1986) demonstrated that Ss were able to evaluate adjectives more quickly when these adjectives were immediately preceded (primed) by attitude objects of similar valence, compared with when these adjectives were primed by attitude objects of opposite valence. Moreover, this effect obtained primarily for attitude objects toward which Ss were presumed to hold highly accessible attitudes, as indexed by evaluation latency. The present research explored the generality of these findings across attitude ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
870
7
21

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 776 publications
(952 citation statements)
references
References 32 publications
54
870
7
21
Order By: Relevance
“…Because the latency of incorrect responses would be difficult to interpret, only correct responses were used in all the subsequent analyses (see Bargh, Chaiken, Govender, & Pratto, 1992;Fazio, 1990). The percentage of errors was 7%.…”
Section: Resultsmentioning
confidence: 99%
“…Because the latency of incorrect responses would be difficult to interpret, only correct responses were used in all the subsequent analyses (see Bargh, Chaiken, Govender, & Pratto, 1992;Fazio, 1990). The percentage of errors was 7%.…”
Section: Resultsmentioning
confidence: 99%
“…Behavioral findings further suggest that emotional stimuli can influence performance on certain tasks even when participants are not consciously aware of the stimuli. Studies using subliminal priming have shown that reaction time is faster when the prime and target are congruent in valence (Bargh et al, 1992) and similarly, subliminal priming effects have been reported with novel, nonrepresentational stimuli presented as targets (Murphy & Zajonc, 1993;Wong & Root, 2003). Importantly, under conditions of restricted attentional resources, emotional stimuli are able to reach conscious awareness even when neutral stimuli cannot (Anderson, 2005;Milders et al, 2006).…”
Section: Introductionmentioning
confidence: 86%
“…Behavioral or outcome beliefs are typically measured by bipolar probability statements linking the behavior to a set of outcomes ("My using condoms will prevent AIDS" with response options unlikely vs. likely; Chan, 1994, p. 84), whereas outcome evaluations are measured by means of bipolar evaluative items (e.g., "Preventing AIDS is …" with response options bad vs. good; Chan, 1994; p. 83). This component of the model is critical when researchers are interested in modifying attitudes because it assumes that attitudes are based on beliefs (but see Bargh, Chaiken, Govender, & Pratto, 1992; Fazio, 1990). However, outcome beliefs and evaluations are not a primary focus of this review as they do not contribute to actions in a direct fashion.…”
mentioning
confidence: 99%